Learners’ Perceptions of Synchronous Written Corrective Feedback in Videoconferenced Collaborative Writing - Papin, Kevin; Michaud, Gabriel (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2023)
Second language (L2) research suggests that synchronous written corrective feedback (SWCF) in online collaborative writing tasks can help improve L2 linguistic knowledge and writing skills. Following the rise of online collaborative writing in the wake of the COVID-19 pandemic, this exploratory study examines L2 learners’ perceptions of receiving SWCF during collaborative writing tasks completed on an online text-editing platform (Google Docs) and mediated by videoconferencing (Zoom). Adult learners (N = 46) enrolled in advanced online French as a Second Language courses took part in two collaborative writing tasks, during which their teachers (N = 3) provided SWCF. Learners’ screen activity was recorded. After the experiment, a perception survey was distributed and selected participants took part in semi-structured interviews to further discuss their experience. Results indicate that learners viewed the provision of SWCF through computer-mediated communication as an effective way to improve their L2 writing compared to traditional, delayed written feedback. Pedagogical implications for the implementation of videoconferences collaborative writing tasks involving teacher SWCF are discussed.